Physical, Chemical, and Biological Pretreatment of Lignocellulose in Oil Palm Empty Fruit Bunches (OPEFB) - Devi, Devi; Ratnasari, Ika Fitriana Dyah; Astutik, Dwi; Widodo, Hery; Ismoyojati, Roni; Sajjad, Nimra (Universitas Ahmad Dahlan, 2024)
Oil Palm Empty Fruit Bunch (OPEFB) constitutes a solid waste generated by the palm oil industry. Empty palm oil bunches contain cellulose or fiber. This component is the primary source for generating valuable products, including fermented sugar, chemicals, liquid fuel, carbon sources, and energy. This research contributed to determine the lignin, hemicellulose, and cellulose content of empty palm oil fruit bunches during biological, physical and chemical Pretreatment, as well as to determine the degradation of lignin, hemicellulose and cellulose. Physical treatment uses steam explosion, chemical treatment uses NaOH and biological treatment uses Trichoderma reesei FNCC 6012. Pretreatment using steam explosion has temperature levels ranging from 120 ℃, 140 ℃, and 160 ℃. Treatments using NaOH consisted of concentrations of 2%, 4%, and 6%, while treatments using Trichoderma reesei were based on fermentation times of 5 days, 10 days, 15 days. This preliminary treatment functions to reduce the lignin levels in empty palm oil fruit bunches. The parameters observed in this research were lignin, hemicellulose and cellulose content. The research results showed that treatment using Steam explosion at temperatures of 140 ℃ and 160℃ was able to reduce lignin levels by 16.03% and 15.90%. Treatment using steam explosion at a temperature of 160 ℃ and Trichoderma reesei for 15 days was able to increase Hemicellulose levels by 35.84% and 36.21%. Treatment using Steam explosion at a temperature of 160℃ gave the best effect on cellulose of 51.09%.